2012
DOI: 10.1530/joe-11-0442
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged interleukin 6 level of protein and energy restricted goats during late gestation: the role of elevated blood nitric oxide

Abstract: Twelve pregnant goats were assigned to three dietary treatments during late gestation, namely control (C: metabolizable energy, 5 . 75 MJ/kg; crude protein, 12 . 6% and dry matter basis), 40% protein restricted (PR) and 40% energy restricted (ER), to examine the effects of nutrient restriction on the immune status of pregnant goats. Plasma was sampled on day 90, 125 and 145 from pregnant goats to determine cytokine production (interleukin 2 (IL2), IL6) and tumor necrosis factor a (TNFa)). Peripheral blood mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our unchanged CRP level in neonates from goats fed with inadequate protein or energy levels suggested that the tissue damage in kids from maternal nutritional restriction were not acute, although the other immune indexes (e.g., immunoglobulins and cytokine expression) were affected by maternal nutritional restriction. He et al (2012a) previously reported that restriction of intake to 40% below the protein or en-ergy requirements of pregnant goats did not affect BW change, thus the imposed nutritional restriction could be considered moderate rather than severe.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our unchanged CRP level in neonates from goats fed with inadequate protein or energy levels suggested that the tissue damage in kids from maternal nutritional restriction were not acute, although the other immune indexes (e.g., immunoglobulins and cytokine expression) were affected by maternal nutritional restriction. He et al (2012a) previously reported that restriction of intake to 40% below the protein or en-ergy requirements of pregnant goats did not affect BW change, thus the imposed nutritional restriction could be considered moderate rather than severe.…”
Section: Discussionmentioning
confidence: 97%
“…The production of IL-6 and tumor necrosis factor α (TNF-α) by bone marrow cells has been reported to be less in malnourished animals (Fock et al, 2007). However, the production of IL-6 by peripheral blood mononuclear cells from PR or ER goats was found to be greater after 48 h of in vitro culture (He et al, 2012a). In addition, Badr and Mohany (2011) reported that off- spring from 50% feed restricted pregnant rats exhibited a reduction in plasma IL-2 and IL-7 compared with offspring from control pregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding goats with a high-concentrate (HC) diet resulted in lower nitric oxide (NO) production compared to the normal group. Typically, increased NO levels are associated with an enhanced pro-inflammatory response to lipopolysaccharides (LPS) [36], which correlates with elevated concentrations of various interleukins. Prior research has demonstrated that elevated IL-6 levels may enhance the permeability of the rumen epithelium and diminish its barrier function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of the literature exists for different species concerning the function of growth factors, cytokines, hormones, and enzymes in the early pregnant uterus and placenta of different species such as cattle [38], sheep [39], goats [40], pigs [41], mares [42,43], bitches [2,44,45], and cats [46]. The present study in cats determined that HIF1A, HIF2A, HIF3A, and VEGF are expressed in all regions of the uterus throughout the pregnancy.…”
Section: Discussionmentioning
confidence: 99%